CCA secure and efficient proxy re-encryption scheme without bilinear pairing. (May 2021) - Prasad, Shilpee; B.R., Purushothama
Abstract: Proxy re-encryption enables the conversion of ciphertext of a message encrypted with one users public key into a ciphertext that could be decrypted by another users private key. Proxy re-encryption can be used as tool for delegation in wide variety of applications. Since proxy re-encryption is used as a primitive for delegation in varied applications, the primitive should be secure and efficient. Also, depending on application scenario, it should satisfy various properties. The proxy re-encryption scheme without bilinear pairing are preferred, as the bilinear pairing is costly operation. We propose an efficient proxy re-encryption scheme without bilinear pairing. The proposed scheme is unidirectional, key optimal, collusion safe, non-interactive, non-transitive, proxy visible, provides original access and satisfies temporary property. The scheme handles the temporary property elegantly compared to the existing schemes without affecting the signing capability of the delegator. Also, the proxy visible property allows the delegatee to prioritize his responses. The proposed scheme is proved to be secure against the chosen ciphertext attack under random oracle model. The proposed scheme is shown to be efficient than the existing schemes.